Eksistensi Hiperbola dan Personifikasi dalam Surah Yasin (Studi Balaghah: Bayan dan Badi') - Pangestu, Puji Sumeh; Sudrajat, Azzahra Emira; Susiawati, Wati; Rojahi, Sahid (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeru Sultan Aji Muhammad Idris Samarinda, 2025)
Surah Yasin has several privileges and virtues for those who read and understand it, in addition to the privileges obtained by those who understand it. Surah Yasin itself also has the privilege of several aspects, one of which is in the linguistic aspect in which it contains a lot of 'only' and other language styles such as hyperbole and personification. This research tries to uncover the existence of hyperbolic language styles and personifications structure contained in the Qur'an especially in Surah Yasin. The research method used by the researcher is a literature study by reading various literature and understanding theories related to and relevant to the topic being studied, with the analysis model using ‘content analysis’ adopted by the researcher from the content analysis model of the Kripperndorff Clause. The results of this research found that there were five verses containing a hyperbolic language style in Surah Yasin, those are in verses 28, 29, 75, 78, and 72. Then five verses were found that contained a personification structure in Surah Yasin, those are in verses 33, 38, 40, 46, and 49.